2017
DOI: 10.1021/acs.orglett.6b03776
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Uncharged Tetra-cyclopeptide Acting as a Transmembrane Carrier: Enhanced Cellular and Nuclear Uptake

Abstract: A small uncharged cyclopeptide scaffold inspired by a natural product and designed to undergo postfunctionalizations was used as a new transmembrane vector. A bioactive and fluorescent triazole aminocoumarin was bound to this carrier to facilitate its moving across cell and subcellular membranes, and this led to an increase in its cell toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Inspired by a natural product FR235222 (Figure ), Hilário et al synthesized a cyclic tetrapeptide and postfunctionalized it with a cargo model, a bioactive and fluorescent triazole aminocoumarin, to test its cytosolic penetration and cytotoxicity. This study successfully demonstrated the ability of this cyclic CPP to deliver small bioactive molecules not only for cytosolic but also for nuclear delivery …”
Section: Biomedical Applications Of Cyclic Cppsmentioning
confidence: 72%
See 1 more Smart Citation
“…Inspired by a natural product FR235222 (Figure ), Hilário et al synthesized a cyclic tetrapeptide and postfunctionalized it with a cargo model, a bioactive and fluorescent triazole aminocoumarin, to test its cytosolic penetration and cytotoxicity. This study successfully demonstrated the ability of this cyclic CPP to deliver small bioactive molecules not only for cytosolic but also for nuclear delivery …”
Section: Biomedical Applications Of Cyclic Cppsmentioning
confidence: 72%
“…The summary of biomedical applications of the cyclic CPPs is presented in Table . We have summarized below some of the highlights of these applications. Intracellular delivery of cargo including drug, protein, phosphopeptide, and bioactive molecules , , Cyclic CPPs can target the nucleus Cyclic CPPs are used as antibacterial or bacteriostatic agents Cyclic CPPs deliver siRNA in cancer cell lines , Cyclic CPP is a promising scaffold for nanoparticle or small bioactive molecule design ,,,, Cyclic CPPs can silence kinase protein, such as KSP and JAK2 in cancer …”
Section: Biomedical Applications Of Cyclic Cppsmentioning
confidence: 99%
“…The repurposing of cell-permeable natural product FR235222 ( 24 , Figure ) by Hilario et al. generated a cyclotetrapeptide scaffold (compound 25 , Figure ) that effectively internalized an aminocoumarin dye and had antiproliferative effects (IC 50 = 0.27 μM against HEK293 cells), presumably by inhibiting the HDAC activity (IC 50 = 35.8 nM) . Another family of cell-permeable macrocycles, the orbitides, comprise a diverse family of ribosomally synthesized and post-translationally modified (RiPP) cyclic peptides. , They tend to be rich in Leu and aromatic residues and highly hydrophobic, lacking N α -methylation but occasionally containing backbone constraining motifs in the form of proline.…”
Section: Application Of Mechanistic Understanding To Design Cell-perm...mentioning
confidence: 99%
“…The flexible aliphatic chain and the (R)-hydroxyl ketone zincbinding group are in one part responsible for the selective inhibition of class I HDACs isoforms [11]. On the other hand, the constrained and uncharged cyclic tetrapeptide moiety confers cell penetration properties, as we have demonstrated on human cells [12]. This moiety is found in natural products [13], and the cell penetration properties can be attributed to its cyclic nature [14][15][16].…”
Section: Introductionmentioning
confidence: 73%
“…Indeed, such a structure could dynamically adopt hydrophobic or hydrophilic conformations depending on the polarity of the medium [17] and thus confer permeability properties that can go beyond the Ro5, especially in terms of molecular weight limitation [18][19][20][21]. In a previous study, we demonstrated that the cyclic tetrapeptide moiety found in FR235222 can transport Wang's fluorescent coumarin triazole (in blue, Figure 1) [22], which has a low cell permeability, into the nucleus through the lipid bilayers [12]. The aim of this work is to demonstrate the ability of this cyclic tetrapeptide to transport this agent through two types of membrane, hydrophilic and hydrophobic membranes, using the Tg cyst as a model and to provide insights into the mechanism involved in its penetration by molecular modeling.…”
Section: Introductionmentioning
confidence: 99%